Synthesis and preparation of thermoplastic silicone elastomer and molecular dynamics simulation of self healing and mechanical properties - Fei, Fan; Chai, Xin; Hu, Wanying; Lu, Wentong; Tian, Hao; Wang, Jincheng (Polymer (Guilford), 2024)
Previous studies have shown that the self-healing properties of modified polydimethylsiloxane (PDMS) elastomer are primarily attributed to hydrogen bonding with modified silica. The addition of modified silica can improve the tensile strength of the PDMS matrix, as the modified silica and modified PDMS blend groups generate more hydrogen bonding interactions, resulting in better self-healing properties. However, as the proportion of silica in the system gradually increases, the rigid particles cause a slight decrease in the tensile property of the material. Consequently, it is crucial to strike a balance between the desired mechanical properties and the self-healing capabilities when investigating this subject matter. To investigate the self-healing behavior of PDMS elastomer, a molecular dynamics technique based on a microcracking model was employed. During the compounding process, isocyanate-modified nanosilica was added to the polysiloxane matrix.The ratio of soft and hard segments, which determines the number of hydrogen bonds, was optimized by varying the silica addition ratio from 1 % to 5 %. The performance of the samples was analyzed using several calculations, including Fraction of Free Volume (FFV), Mean Square Displacement function (MSD), and Relative Concentration (RC).The results revealed that the highest self-healing performance and fastest self-healing rate were achieved when the silica addition ratio was 3 %. All tested structures displayed efficient healing within a short time frame. The primary hydrogen bonding exchanges occurred between the urea and UPy groups within the system.Furthermore, the experimental results aligned with the findings from the molecular dynamics simulations, thereby validating this study. [Display omitted] •By blending UPy-NCO modified silica with modified PDMS, an elastomer with outstanding self-healing capabilities was successfully synthesized.•This method not only endowed the elastomer with self-healing property but also enhanced its tensile strength and elongation at break.•Through molecular dynamics simulation, the self-healing mechanism of the elastomer was further elucidated.